Extracellular aggregated Cu/Zn superoxide dismutase activates microglia to give a cytotoxic phenotype. Issue 3 (22nd December 2012) - Roberts, Kate; Zeineddine, Rafaa; Corcoran, Lisa; Li, Wen; Campbell, Iain L.; Yerbury, Justin J.
Abstract A large body of literature suggests that amyotrophic lateral sclerosis (ALS) pathology is intimately linked with neuroinflammation, specifically activation and recruitment of microglia and astrocytes. The actual cause of gliosis is unclear. Extracellular Cu/Zn superoxide dismutase (SOD1) has recently been shown to activate microglia in a CD14 dependant mechanism providing one potential pathway by which glial cells become activated. As protein inclusions are thought to be an important part of ALS pathology and are associated with all forms of ALS, we sought to determine if aggregated SOD1 would activate microglia. Recombinant SOD1 was aggregated and this, or monomeric forms of SOD1 were then added to EOC.13 microglial cells or primary microglial cells in culture. Although monomeric mutant SOD1 has been shown to promote microglial activation in the past, we found that aggregated SOD1 was able to much more efficiently activate microglia in culture when compared with the unaggregated form of mutant SOD1. In addition to CD14 dependant pathways, aggregated SOD1 also bound to the surface of glial cells and was internalized in a lipid raft and scavenger receptor dependent manner. We have for the first time shown that aggregated mutant SOD1 potently activates microglia. These results suggest that there may be a potential link between protein aggregation and microglial activation in ALS. © 2012 Wiley Periodicals, Inc.